“Sulle strade del Po”. Dalle bonifiche dei monaci benedettini ai giorni nostri - Marzorati, Paola (Ri-Vista. Research for landscape architecture, 2015)
The province of Mantova, in collaboration with Regione Lombardia and the reclamation and irrigation local authorities, promoted the realization of some bike and pathways of a great landscape value along the main rivers and canals in the Oltrepo mantovano area. One of those is the cycling track called “On the ways of Po river”, travelled by the author of this article in a warm afternoon of may (2006). The track curls along the flood plain landscapes and was built on the main bank of Po river. The goal of this project is to create a greenway that connects the main core areas of the provincial ecological network. The itinerary of a great landscape value integrates the last strip of nature preserved in San Colombano park, with the important historical and cultural heritage spreaded all over the Oltrepo mantovano, as the Monastery of Polirone in San Benedetto Po and the drainage units of Moglia di Sermide and Revere.